CHARACTERISTICS OF FUNDAMENTAL CULTURAL SCIENCE (World Bulletin of Social Sciences, 2024)
This article discusses the importance of modern cultural studies, its current topics, main goals and tasks
Keywords: culture; cultural history and theory; cultural activity; cultural space